Contact toxicity and repellency of lemongrass, spearmint, rosemary oils and their major bioactive compounds on destroyer ants (Trichomyrmex destructor) under laboratory conditions - Lekhnath Kafle; Ai-Yun Chung (Discover Applied Sciences)
Abstract The destroyer ant (Trichomyrmex destructor) builds aggressive nests in an indoor environment, damaging machinery and structures, and poses threats to humans. Plants contain secondary metabolites that may be toxic to insect pests. In this study, the contact toxicity and repellency of three plants—lemongrass (Cymbopogon flexuosus), spearmint (Mentha spicata), and rosemary (Rosmarinus officinalis)—and their bioactive compounds—citral, carvone, and camphor—to destroyer ants were investigated. Under laboratory conditions, contact toxicity of all test materials was assessed at six different application rates (0.2, 0.4, 0.6, 0.8, 1, and 2 μL/cm2), and the repellency of essential oils and two compounds (citral and carvone) against destroyer ants was assessed at three different application rates (0.8, 1, and 1.2 μL/cm2). Based on the results, all essential oils and bioactive compounds demonstrated strong contact toxicity against destroyer ants, caused mortality rates 80–90% within 12 h. Among the essential oils tested, lemongrass oil was the most toxic to the ants, followed by spearmint oil and rosemary oil. Similarly, citral was the most toxic bioactive compound to the ants among the tested compounds, followed by carvone and camphor. For repellency, both test materials demonstrated a repellency rate of 74–90% against destroyer ants within two-hours. According to this study, lemongrass, spearmint, and rosemary essential oils, along with their bioactive compounds, can effectively eliminate and repel destroyer ants, suggesting that these natural ingredients may be a viable alternative to synthetic insecticides in controlling the populations of these destructive ants.